Catalyst effect on steryl glucosides concentration in palm-based biodiesel during transesterification process - F. K., Azmi; Muhammad Nor Fazli, Abd Malek; Maniam, Gaanty Pragas (Penerbit Universiti Malaysia Pahang, 2024)
In this study, biodiesel was synthesized from crude palm oil through a double-step transesterification process using a CaO-SiO₂ bi-catalyst. The catalyst was designed to serve dual purposes: facilitating the transesterification reaction and removing steryl glucosides (SGs), a critical impurity in biodiesel. The process optimization was carried out using Central Composite Design to achieve maximum fatty acid methyl ester conversion. The synthesized biodiesel was characterized for density (0.863 g/cm³), viscosity (5 mPa·s), iodine value (19.572 g/100g), acid value (0.437 mg KOH/g), and conversion efficiency (81.71%), confirming its compliance with biodiesel standards. Catalyst characterization through SEM, XRD, BET, and FTIR analyses revealed an amorphous structure, high surface area (86.81 m²/g), and functional groups suitable for SG removal and catalytic activity. UV-visible spectroscopy confirmed an SG removal efficiency of 79.15 %. This study demonstrates the effectiveness of the CaO-SiO₂ bi-catalyst in integrating biodiesel synthesis and impurity removal in a single reaction, offering a simplified and efficient approach to biodiesel production.